A Review of Use of Enantiomers in Homeopathy. (15th August 2012) - Kuzeff, R. M.
Abstract : This paper reviews publications of laboratory experiments using pairs of enantiomers in homeopathy. Many molecules in nature have geometry which enables them to exist as nonsuperimposable mirror images or enantiomers. Modulation of toxicity of such molecules provides possibility for therapeutics, since they target multiple points in biochemical pathways. It was hypothesized that toxicity of a chemical agent could be counteracted by a homeopathic preparation of the enantiomer of the chemical agent (patents applied for: PCT/AU2003/000219-PCT/AU2008/001611). A diverse body of data, including controlled laboratory studies, supports the conclusion that toxicity of optical isomers may be inhibited by homeopathic enantiomer preparations. These data were obtained with minimal or no pretesting to determine optimal test solutions. Inhibition of the excitotoxic neurotransmitter L-glutamic acid with homeopathic preparations of D-glutamic acid indicates the latter may be of use for amelioration of symptoms of disturbances of mood. Similarly, homeopathic preparation of (+)-nicotine may be of use for inhibition of effects of nicotine in tobacco.